Efektivitas Pelaksanaan Kebijakan Otonomi Khusus Dalam Rangka Meningkatkan Kesejahteraan Masyarakat Di Distrik jayapura Utara Kota Jayapura - Torobi, Ketreda Ludia (JURNAL ADMINISTRASI PUBLIK, 2014)
In accordance with the mandate of the 1945 Constitution, the Republic of Indonesia as a unitary state adheres to the principle of decentralization in governance by providing opportunities for local flexibility to organize local autonomy. Local governments are authorized to regulate and manage their own affairs according to the principles of autonomy and assistance. This study used qualitative methods. Data source or informant study as many as 22 people were taken from several related elements are Dstrik Government (District Chief) 1, 7 People Village Government and Papuans 14 people. Collecting data using questionnaires, interviews and documentation. The data analysis technique used is interactive analysis. Based on the research it can be concluded that the effectiveness of the Papua Special Autonomy policy, viewed from the aspect of education has not been effective, while aspects of health, economy, culture and religion have been quite effective Keywords: Special Autonomy in Developing Welfare